A retrospective review of 101 operatively treated radial neck fractures in children and analysis of risk factors for functional outcomes. Issue 10 (October 2022) - Yang, Lei; Yang, Xiaodong; Zuo, Jingjing; Wang, Daoxi; Li, Lang; Tang, Xueyang
Highlights: Radial neck fracture is a rare injury in childhood, but with a high rate of associated injuries, among which the ulnar fracture is the most common one. Radial nerve palsy is a common combined injury in pediatric radial neck fracture, which was significantly associated with the severity of fractures. Considering the significant correlation between fracture severity and open reduction rate, fracture severity classified as Judet type IV and open surgical method were independent predictors for unsatisfactory functional outcomes. Abstract: Introduction: Radial neck fracture is a less common injury in childhood and many factors are associated with the final functional outcomes. This study aimed to describe the clinical and radiological results of the patients with radial neck fractures treated surgically and assess the potential risk factors for poor functional outcomes. Patients and Methods: This study enrolled 101 children with radial neck fracture and treated surgically at our department. Patients were followed up at least three years and assessed clinically and radiographically. The primary outcome of this study was the functional outcome assessed by using Metaizeau criteria and the secondary outcome was complications of radial head necrosis, postoperative radial nerve palsy, bone union, infection, and skin irritation. Related risk factors for unsatisfactory functional outcomes were recorded and analyzed by multivariable logistic regression. Results: In total, 101 patients with 101 elbows (44 on the left side, 57 on the right side) were evaluated in our study, including 55 females (54.5%) and 46 males (45.5%), with a mean age of 7.5±2.7 years old (range, 3 to 14 years). There were 65.3% excellent (66 cases), 18.8% good (19 cases), 11.9% fair (12 cases), and 4.0% bad (4 cases) results in these patients. The rate of satisfactory outcome was 65.3% (66/101) and the rate of "unsatisfactory outcome" was 34.7% (35/101). Complications included postoperative radial nerve palsies in 15 cases (14.9%), radial head necrosis in 4 cases (4.0%), skin irritation due to the nail-end in 5 cases (5.0%), infection in 2 cases (2.0%), and bone nonunion in 1 patient (1.0%). Only Judet type (OR, 5.78; CI, 1.72-19.39, p=0.005) and surgical method (OR, 12.68; CI, 2.55-63.06, p=0.002) were independent risk factors for the unsatisfactory functional outcomes. Conclusions: Closed reduction with intramedullary fixation is a primary treatment for type III and IV radial neck fractures in children. Fracture severity classified as Judet type IV and open surgical method were independent predictors for unsatisfactory functional outcomes.